Optimizing MR-Guided Radiotherapy for Breast Cancer Patients - Groot Koerkamp, Maureen L.; Vasmel, Jeanine E.; Russell, Nicola S.; Shaitelman, Simona F.; Anandadas, Carmel N.; Currey, Adam; Vesprini, Danny; Keller, Brian M.; De-Colle, Chiara; Han, Kathy; Braunstein, Lior Z.; Mahmood, Faisal; et al. (Frontiers in Oncology, 2020)
Current research in radiotherapy for breast cancer is evaluating neoadjuvant as opposed to adjuvant partial breast irradiation with the aim of reducing the volume of breast tissue irradiated and therefore the risk of late treatment-related toxicity. The development of MR-guided radiotherapy, including dedicated MR-guided radiotherapy systems (hybrid machines combining an MR-scanner with a linear accelerator (MR-linac) or 60 Co sources) could potentially reduce the irradiated volume even further by improving tumour visibility before and during each radiotherapy treatment. In this position paper we discuss MR-guidance in relation to each step of the breast radiotherapy planning and treatment pathway, focussing on the application of MR-guided radiotherapy to neoadjuvant partial breast irradiation.